Antibacterial and antioxidant potential of biosynthesized silver nanoparticles using aqueous root extract of Angilica glauca. Issue 10 (10th August 2020) - Riaz, Muhammad; Altaf, Muhammad; Ayaz, Muhammad; Sherkheli, Muhammad Azhar; Islam, Arshad
Abstract: Herein, we report the green synthesis of silver nanoparticles using the aqueous extract of root of Angilica glauca Edgew. UV-vis and FT-IR spectroscopies, X-ray diffraction analysis and scanning electron microscopy technique were employed to structurally and morphologically characterize the green synthesized silver nanoparticles. The nanoparticles were found to be spherical in shape with an average size of ∼21 nm. The extract was found to be rich in phenolic and flavonoid contents. Both the extract and the extract-loaded silver nanoparticles inhibited the growth of both Pseudomonas aeruginosa (inhibition zone 13.0 ± 1.6 and 4.0 ± 0.9 mm, respectively) and Escherichia coli (inhibition zone 12.0 ± 1.1 and 3.0 ± 0.6 mm, respectively) at 9.0 µg/mL. The antioxidant potential of the extract (IC50 = 30.79 ± 3.2 µg/mL) was determined via DPPH radical scavenging assay. These nanoparticles are concluded to possess antibacterial potentials.